Optimal shot peening residual stress profile for fatigue. (December 2021) - Aguado-Montero, S.; Vázquez, J.; Navarro, C.; Domínguez, J.
Abstract: Shot peening (SP) is frequently used as a palliative measure against metal fatigue in many engineering components. The performance of this surface treatment depends on different factors including the material, shape and loading conditions of the component, as well as process parameters. Fatigue improvement due to SP depends to a great extent upon the in-depth compressive residual stress profile produced in the specimen. In this work, we study the optimum shape for a residual stress profile in terms of fatigue behaviour. For this task, we assume a residual stress profile that is qualitatively similar to that produced by SP in many metals. Based on this generic profile, we analyse the optimum shape for two simple, but noteworthy, fatigue cases: plain fatigue and notch fatigue. The analysis is conducted in the "fatigue damage tolerance design" framework, in which a certain initial defect is assumed to be present in the component under study. Highlights: The optimum shot peening residual stress profile for fatigue behaviour is analysed. Optimum profiles for plain and notched fatigue situations are studied. Shot peening residual stress profile is modelled using a sinusoidal decay function. A new set of parameters modelling the sinusoidal decay function is proposed.